Disaster Coverage Predication for the Emerging Tethered Balloon Technology: Capability for Preparedness, Detection, Mitigation, and Response - Alsamhi S.H.; Samar Ansari M.; Rajput N.S. (My University, 2025)
Objective: A disaster is a consequence of natural hazards and terrorist acts, which have significant potential to disrupt the entire wireless communication infrastructure. Therefore, the essential rescue squads and recovery operations during a catastrophic event will be severely debilitated. To provide efficient communication services, and to reduce casualty mortality and morbidity during the catastrophic events, we proposed the Tethered Balloon technology for disaster preparedness, detection, mitigation, and recovery assessment. Methods: The proposed Tethered Balloon is applicable to any type of disaster except for storms. The Tethered Balloon is being actively researched and developed as a simple solution to improve the performance of rescues, facilities, and services of emergency medical communication in the disaster area. The most important requirement for rescue and relief teams during or after the disaster is a high quality of service of delivery communication services to save people's lives. Results: Using our proposed technology, we report that the Tethered Balloon has a large disaster coverage area. Therefore, the rescue and research teams are given higher priority, and their performance significantly improved in the particular coverage area. Conclusions: Tethered Balloon features made it suitable for disaster preparedness, mitigation, and recovery. The performance of rescue and relief teams was effective and efficient before and after the disaster as well as can be continued to coordinate the relief teams until disaster recovery. Copyright © 2017 Society for Disaster Medicine and Public Health, Inc.